Multivariable Analysis and Phenotypic Diversity Studied for Some Barley Genotypes under Heat Stress (London Journal of Research In Science: Natural and Formal, 2025)
Heat stress is one of most domineering abiotic stress influences that border barley production. Herein, three different field screening locations were carried out at Sakha, Mallawi and New-valley research stations, to identify the response of ten barley genotypes to different temperatures degrees using phenotypic diversity and, multivariable analysis during two consecutive seasons 2020/2021 and 2021/2022 under different temperatures degrees. Heat stress index (HI) activated a reduction in all traits ranged from lowest average reduction in plant height PH by (5.43 and 20.37%) to highest average reduction in no. of tillers /m2TM by (14.49 and 40.83 %) under Malawi (T2) and New Valley (T3) locations respectively as camper by Sakha, also high temperature enhancement all the genotypes to quicken flowering and days to maturity by average (7.24 and 8.35 %) under New Valley. Days to heading HD and to maturity MD exhibited a strong and significant negative relationship with all studied traits Loading principal component analysis PCA accounted 86.1% of the total variability, which PCA2 clarified 24.2 % of the total variability influenced by HD and MD which placed in the left side (negative). Scatter plot of PCA categorizing all the barley genotypes in four groups indicated that the Egyptian barley genotypes (Giza 137, Giza 138, line5, line 1 and line 3) were separate from the other genotypes and located in the right side with of PCA1 analysis cluster with a significant distance which could be considered as a heat tolerance genotypes. A cluster heatmap according their resulted form all studied traits showing that the ten barley genotypes were clustered into two main clusters, Giza 137, Giza 138, line5, line 1 and line 3 were the most closed genotypes together due to their tolerance to heat stress while line 2 and line 8 were the most closed genotypes together due to their sensitive to heat stress. Thus, we could use them as a source for future barley breeding programs for heat stress such as important step to get a new genotype with high heat tolerance and high yield.
Keywords: PCA; Hordeum vulgar; phenotypic diversity - heat stress index HI; heatmap analysis